2015
DOI: 10.17678/beuscitech.47145
|View full text |Cite
|
Sign up to set email alerts
|

Poultry meat consumption and consumer trends in Turkey

Abstract: This study was conducted by Poultry Research Institute to determine the poultry meat consumption and consumer trends in Turkey. With this aim questionnaire forms composed of 26 questions were prepared. This questionnaire study was conducted with 2.241 families, which represent the consumer profile of Turkey, supplied by Turkish Statistical Institute. Data obtained from the questionnaire were evaluated by using SPSS programme (SPSS 17). 98.26% of the participants were determined to consume poultry meat. Yearly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 2 publications
2
3
0
Order By: Relevance
“…In contrast, most respondents (77.3%) were dissatisfied with the hygienic conditions adopted by roadside vendors. These findings were in accordance with the earlier finding of Durmus et al (2012) [5] , who reported dissatisfaction of 61% of participants since poultry meat production was not inspected adequately in Turkey. Singh et al (2019) [10] reported that the respondents (68.50-88.50%) from all four zones of Ludhiana were not satisfied with the hygienic conditions adopted by roadside vendors.…”
Section: Consumer Awareness and Hygiene Considerations Regarding Meatsupporting
confidence: 93%
See 1 more Smart Citation
“…In contrast, most respondents (77.3%) were dissatisfied with the hygienic conditions adopted by roadside vendors. These findings were in accordance with the earlier finding of Durmus et al (2012) [5] , who reported dissatisfaction of 61% of participants since poultry meat production was not inspected adequately in Turkey. Singh et al (2019) [10] reported that the respondents (68.50-88.50%) from all four zones of Ludhiana were not satisfied with the hygienic conditions adopted by roadside vendors.…”
Section: Consumer Awareness and Hygiene Considerations Regarding Meatsupporting
confidence: 93%
“…Most respondents (66.3%) reported that the meat (goat/sheep meat/poultry/pork) was purchased from the shop, as against 33.7% of consumers who think the meat was not processed hygienically. The finding was in line with earlier findings of Raju and Suryanarayana (2005) [5] , Singh et al (2019) [10] and Waghmare et al (2021) [15] , who reported that nearly 42.78% of consumers were concerned about the meat retail shop's cleanliness and hygienic condition when they buy non-vegetarian products. This shows that consumers are concerned about food safety but unaware of the quality guidelines and standards.…”
Section: Consumer Awareness and Hygiene Considerations Regarding Meatsupporting
confidence: 91%
“…Chickens are indicators of T. gondii strain prevalence in a domestic or peridomestic environment and several studies have examined the distribution of T. gondii genotypes in chickens in many countries, including Brazil [14, 23]. The yearly poultry meat consumption per capita in Brazil is estimated to be 31·66 kg and the importance of these studies is because the toxoplasmosis pathogenicity is also determined by T. gondii strain virulence, with repercussions for the quality of life in the population, among other foodborne pathogens, as has been demonstrated in the USA [2426].…”
Section: Discussionmentioning
confidence: 99%
“…Even though there were several studies conducted to determine the factors affecting the chicken meat consumption and consumer preference in Turkey, limited data were available related with consumers' handling of raw chicken meat after the purchase and possible effects of the handling practices on the quality of the chicken meats ( Uzundumlu et al, 2011a , b ; Durmus et al, 2012 ; Senturk and Guler, 2012 ; Aral et al, 2013 ; Senturk, 2015 ). Therefore the objective of this study was to determine the effects of the most common thawing practices used by the consumers at home on some quality characteristics of the chicken meat.…”
Section: Introductionmentioning
confidence: 99%